Drought response and urban-pollinator attractiveness of ornamental plant species - Quinanzoni, Margaux; Marcolet, David; Michelot-Antalik, Alice (Basic and applied ecology, 2024)
Faced with pollinator declines, cities could serve as refuges for biodiversity conservation by managing floral resources in public green spaces. Ornamental plants could play an important role in attracting pollinators because they form part of urban floral management. However, knowledge of how their floral traits respond to drought is lacking, and it is unknown whether they will be suitable for pollinators under future climates. The main objective of this study was to determine the covariation of floral traits of ornamental plant species and effects of drought on them. To this end, in a city greenhouse we measured floral traits of eight ornamental species commonly used in urban green spaces in France. We subjected the plants to a control treatment or a drought treatment, reducing the volume and frequency of watering. We observed interspecific variability in floral traits among these species and a change in covariation between the traits pollen quantity and nectar quantity in the drought treatment. Drought influenced morphological traits related to floral display more than other floral traits, with mean decreases of 28 % in floral height, 35 % in floral area and 58 % in the number of floral units. Ornamental plants seemed attractive to different morphotypes of pollinators depending on their floral unit number, nectar sugar concentration or nectar tube depth, with most visits made by Hymenoptera. These results are expected to encourage green-space managers to select urban plants according to their functional characteristics and adapt their choice of plants to climate change.